2015
DOI: 10.1002/stc.1745
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of fiber Bragg grating strain sensor in dynamic tests of small-scale dam model

Abstract: SUMMARYFor the low strength of model material, it is difficult to test the deformation of the small-scale dam model during shaking table tests. Based on the principle friction, a type of fiber Bragg grating (FBG) strain sensor with enhanced strain sensitivity was developed to measure the strain of low-strength material. The principle of the small-scale FBG strain sensor and its characteristics of strain transferring were discussed using a calibration test. Dynamic strain and residual strain of dam model were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A previous study [34,35] has shown that the stress transfer loss between the fiber and neoprene adhesive can be neglected when the adhesive thickness is less than the diameter of the fiber, and the relative deformation of the grippers at both ends of FBG is also the deformation of FBG, which are given as…”
Section: Fbg Strain Sensor Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study [34,35] has shown that the stress transfer loss between the fiber and neoprene adhesive can be neglected when the adhesive thickness is less than the diameter of the fiber, and the relative deformation of the grippers at both ends of FBG is also the deformation of FBG, which are given as…”
Section: Fbg Strain Sensor Designmentioning
confidence: 99%
“…where L, , and are the distance between the two cubic supports and the gripper and FBG lengths, respectively; , , , and are the elasticity modulus and section areas of metal tube and fiber, respectively; and are, respectively, the tensile forces in gripper tubes and FBG. Because the tensile forces ( = ) are constant throughout the FBG strain sensor, the strain ratio between the gripper tube and FBG is given as [34] = Δ / Δ / =…”
Section: Fbg Strain Sensor Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these studies have significantly contributed to an understanding of subgrade deformation properties and processes and could be quite promising approaches if applied under actual field conditions using advanced monitoring devices of high accuracy. In recent years, sensors based on fiber Bragg gratings (FBGs) have been applied widely [15][16][17][18][19][20][21] since they were first introduced by Hill et al 22 owing to their numerous advantages such as high sensitivity, lightweight, corrosion resistance, low optical loss, and resistance to electromagnetic interference, with real-time and remote monitoring capabilities. 23,24 This study presents the development of an implanted cantilever sensing beam based on FBGs for subgrade deformation monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most widely used fiber sensing element, the FBG (Fiber Bragg grating) has been proven to be very effective because of its distinguishing advantages, such as immunity to electromagnetic interference and optical power fluctuations, high resistance to hostile environments, no zero temperature drift and the fact that multiple FBGs can be arrayed along a single optical fiber [5]. In the past two decades, FBG sensors have been widely used in structural health monitoring including mechanical equipment [6], aircraft [7], slope [8], [9], dam [10], etc, and other areas such as humidity [11] and biomedicine [12]. In these applications, strain measurement is essential and the most widely needed.…”
Section: Introductionmentioning
confidence: 99%